2018
DOI: 10.1002/prca.201800129
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoproteomic Identification of Noncarbohydrate Antigens Eliciting Graft‐Specific Adaptive Immune Responses in Patients with Bovine Pericardial Bioprosthetic Heart Valves

Abstract: Purpose: This case-control retrospective discovery study is to identify antigenic bovine pericardium (BP) proteins that stimulate graft-specific humoral immune response in patients implanted with glutaraldehyde fixed bovine pericardial (GFBP) heart valves. Experimental design: Banked serum is collected from age-and sex-matched patients who received either a GFBP or mechanical heart valve replacement. Serum IgG is isolated and used to generate poly-polyclonal antibody affinity chromatography columns from each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Nevertheless, it is noteworthy to mention once more that the sole removal of carbohydrates might not be sufficient to prevent chronic graft rejection; indeed, further studies will be necessary to investigate the appropriate removal of SLA class I molecules as well as non‐carbohydrate xenoantigens reported in the literature, including both proteins and lipids 17,21 . Nonetheless, SLA class I molecules and identified non‐carbohydrates xenoantigens are part of the cell membrane or are located in the subcellular space, and since cells and cellular debris are destroyed and washed out by decellularization, these molecules should not play a role anymore in decellularized tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it is noteworthy to mention once more that the sole removal of carbohydrates might not be sufficient to prevent chronic graft rejection; indeed, further studies will be necessary to investigate the appropriate removal of SLA class I molecules as well as non‐carbohydrate xenoantigens reported in the literature, including both proteins and lipids 17,21 . Nonetheless, SLA class I molecules and identified non‐carbohydrates xenoantigens are part of the cell membrane or are located in the subcellular space, and since cells and cellular debris are destroyed and washed out by decellularization, these molecules should not play a role anymore in decellularized tissues.…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, non-self minor histocompatibility antigens, associated with MHC, have been reported to be recognized by T cells, initiating immune rejection. 17,19,20 Gates et al 21 In addition to the above-mentioned protein xenoantigens, carbohydrate antigens seem to play a major role in tissue immunogenicity, due to their large variety within and between species, much greater than that of proteins. 22 Carbohydrates like galactose-alpha-1,3-galactose (α-Gal) and N-glycolylneuraminic acid (Neu5Gc) were identified as responsible structures for hyperacute or acute immune rejection of the transplant by pig-to-human transplantation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…165,166 Indeed for example, in human patients receiving GTA-fixed heart valves, chronic immune responses toward 19 individual non-HLA antigens were recently reported. 167 Similarly, GTA-fixed heart valves explanted due to development of structural valve deterioration have been shown to be universally positive for non-a-Gal IgG presence. 89,168 GTA fixation is also associated with alterations in ECM scaffold mechanical properties and renders the resultant biomaterial prone to calcification due to free aldehyde residues in the resultant tissue.…”
Section: Overcoming Failure Mechanisms In Vascular Ecm Scaffoldsmentioning
confidence: 98%
“…The additional two immunogenic carbohydrate antigens that have been identified are N-glycolylneuramic acid (Neu5Gc) antigen (Lee et al, 2016;Reuven et al, 2016) and the Sid blood group antigen (Sda) (Li, 2019). Apart from carbohydrate antigens, Katherine et al (Gates et al, 2019) have identified 19 specific protein antigens from GLUT fixed bovine pericardial heart valves that stimulate the graft-specific humoral immune response in patients. Intriguingly, they found calcium-binding proteins were the most highly over-represented biological function of antigens, but such antibody-binding effect of those proteins on BHV calcification is yet to be elucidated.…”
Section: Immune/inflammatory Responsementioning
confidence: 99%